PENGARUH REKRUTMEN, PENEMPATAN DAN PELATIHAN KERJA TERHADAP KINERJA KARYAWAN PT. DARUSALLAM BERLIAN MOTOR - Ayi Satria Yudha; Muhammad Ridha Ramli; Anika Dija (SI-MEN, 2023)
The purpose of this study was to determine the magnitude of the influence of recruitment, placement and training of employees on the performance of PT. Darussalam Berlian Motors either simultaneously or partially. This study used quantitative methods with a population of 70 employees. The sampling technique is a saturated sample (census method), where all employees are used as a sample. Data collection was carried out by distributing questionnaires to respondents and processed using the SPSS statistical tool version 26.0. Testing the hypothesis using multiple linear regression analysis, F test (simultaneous) and t test (partial) is intended to determine the effect of the independent variables on the dependent variable at the 95% confidence level. The results showed that partially the recruitment variable had a significant and significant effect on employee performance with t count (7.682) greater than t table (1.997). Placement variable has significant impact on employee performance with t count (2.381) greater than t table (1.997). and Job training has a significant effect on employee performance with t count (3.505) greater than t table (1.997). Simultaneously the variables Recruitment, Placement, and job training have a significant influence on Employee Performance with an F count (33.867) greater than F tabe1 (2.511). It can be concluded that both partially and simultaneously the Recruitment, Placement, and Job Training variables have a significant and significant effect on Employee Performance at PT Darussalam Berlian Motor.